2001
DOI: 10.1002/etc.5620200712
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring river sediments contaminated predominantly with polyaromatic hydrocarbons by chemical and in vitro bioassay techniques

Abstract: Extracts of sediment samples collected from the Morava River and its tributaries (Czech Republic) were examined for mutagenic, dioxin-like, and estrogenic activities. Moreover, the human leukemic HL-60 cell line was tested as a potential model for the detection of effects of environmental contaminants on cell proliferation and differentiation processes. Analytical data indicate that the sediments were contaminated predominantly with polycyclic aromatic hydrocarbons (PAHs) and phthalate esters. The sums of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 47 publications
2
30
1
3
Order By: Relevance
“…The PAH concentrations in surface sediments from the Jialu River in this study are similar to those detected in the River Gomti, India (Tripathi et al 2009) and the Yellow River, China (Xu et al 2007), and higher than those found at the Yalujiang River, China (Wu et al 2003), the Sava River, Serbia (Crnković et al 2008), the Luan River, China (Bai et al 2008), the Daliao River, China and the Gao-Ping River, Taiwan (Doong and Lin 2004). However, the levels were lower than those reported in the Zhujiang River, China (Mai et al 2002), the Passaic River, USA (Huntley et al 1995) and the Morava River, Czech Republic (Vondracek et al 2001).…”
Section: Concentrations and Distribution Of Pahsmentioning
confidence: 53%
“…The PAH concentrations in surface sediments from the Jialu River in this study are similar to those detected in the River Gomti, India (Tripathi et al 2009) and the Yellow River, China (Xu et al 2007), and higher than those found at the Yalujiang River, China (Wu et al 2003), the Sava River, Serbia (Crnković et al 2008), the Luan River, China (Bai et al 2008), the Daliao River, China and the Gao-Ping River, Taiwan (Doong and Lin 2004). However, the levels were lower than those reported in the Zhujiang River, China (Mai et al 2002), the Passaic River, USA (Huntley et al 1995) and the Morava River, Czech Republic (Vondracek et al 2001).…”
Section: Concentrations and Distribution Of Pahsmentioning
confidence: 53%
“…Except in March 2010, when the peak PAH concentration was recorded, PAH concentrations measured in the sediments of the Vène river were in the same range as concentrations observed in other French Mediterranean rivers (Table 4). Although this high PAH concentration (10,188 ng/g dw) was lower than the concentrations of up to 23,078 ng/g dw measured in rivers in dense urban and industrial areas in France (Kinani et al, 2010), this PAH concentration in the Vène river was in the range of concentrations observed in industrial areas: 636-13,205 ng/g dw (Vondracek et al, 2001) and 5.3-7700 ng/g dw (Koh et al, 2004) and could consequently be toxic for organisms.…”
Section: Bdi ¼ ½Mbt þ ½Dbt ½Tbtcontrasting
confidence: 46%
“…Sie zeichnet sich durch sehr hohe Trennschärfe und sehr gute Reproduzierbarkeit aus, was eine automatisierte Vielfachinjektion ermöglicht und damit das Problem der geringeren isolierten Stoffmenge pro Injektion ausgleicht. (Ames et al, 1975;Samoiloff et al, 1983;DeMarini et al, 1994) Ames Fluktuationstest in Flüssigkultur (Mikrotiterplatten) (Pérez et al, 2003;Flückiger-Isler et al, 2004) Mutatox: Rückmutation einer Dunkelmutante von Vibrio fischeri (Ho and Quinn, 1993;Thomas et al, 2002a) Mutagenitätstests mit menschlichen h1A1v2 B-Lymphoblastoid-Zellen mit constitutiver Überexpression der Oxygenase P4501A1 (Durant et al, 1998;Hannigan et al, 1998) Ah-Rezeptor-vermittelte Wirkung Induktion von 7-Ethoxyresorufin-O-Deethylase in Leberzelllinien von Fischen (RTL-W1, PLHC-1) und Ratten (H4IIE) (Safe, 1986;Brack et al 2002;Gale et al, 2000;Hilscherova et al, 2001) Luziferase-Aktivität in rekombinanter Zelllinie H4IIE-luc (CALUX) Vondracek et al, 2001) Estrogene Aktivität Zelltest mit menschlichen Brustkrebszellen (MCF-7) Zelltest mit menschlichen Brustkrebszellen mit rekombinantem RezeptorReporter-Gen (MCF-7-luc oder MVLN) (Soto et al, 1995) (Vondracek et al, 2001 Hefe-basierter Zelltest mit recombinantem Östrogen-Rezeptor-Reporter-Gen (YES) (Thomas et al, 2004) Androgene Aktivität Hefe-basierter Zelltest mit rekombinantem Androgen-Rezeptor-Reporter-Gen (Thomas et al, 2004;Thomas et al, 2002b) Zellproliferation und Differenzierung…”
Section: Fraktionierungunclassified
“…Menschliche Leukämiezellen (HL-60) oder Rattenleberepitheliumzellen (WB-F344) (Vondracek et al, 2001;Vondracek et al, 2004) GJIC-Hemmung Hemmung der interzellulären Kommunikation bei WB-F344 und Aufhebung der Wachstumshemmung durch Zellkontakt (Tumorpromotion) (Vondracek et al, 2004) Immuntoxizität Hemmung der Lymphoid-Entwicklung in Thymuszellen von Mausföten (C57BL/6) Phagozytosetest Bursttest (Engwall et al, 1997) Entzündungsförderung Cytokin-Produktion in peripheren mononukleären Blutzellen (Wichmann et al, 2004) Prinzipiell sind alle in der Umweltforschung eingesetzten Fraktionierungsverfahren für Lebensmittelextrakte geeignet.…”
Section: Fraktionierungunclassified